PEMBUATAN MAKET GEDUNG DIPLOMA TEKNIK SIPIL SEKOLAH VOKASI UNIVERSITAS GADJAH MADA - , RISKY FAUZI SATRIA P ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Mockups is useful for visualizing object with a smaller scale. It is aiming to describe the building of Civil Engineering Diploma in accordance with circumstance environment as well as explaining the shape of mockups presentation with difference touch. This mockups visualizes Civil Engineering Diploma with 1:100 scales